Produksi Dan Nilai Ekonomi Usaha Ternak Domba Sebagai Sumber Pendapatan Peternak: Tinjauan Literatur : Production and Economic Value of Sheep Farming as a Source of Farmers’ Income: A Literature Review - Supardi Rusdiana; Diky Ramdani; Unang Yunasaf; Chalid Talib; Amam (Journal of Economic, Public, and Accounting (JEPA), 2026)
Sheep farming plays an important role as a source of farmers’ income. However, this activity has generally not yet become the main enterprise, resulting in relatively low farmer earnings. To achieve successful outcomes, production management must be improved by strengthening technical and managerial capacities, including feed, reproduction, health, and marketing management. This study reviews the production and economic value of sheep farming and evaluates its financial feasibility across different scales. The analysis was conducted through a literature review of accredited scientific articles, secondary livestock statistics, and field observations in sheep farming centers. The methods applied include descriptive, comparative, and financial feasibility analyses, using the R/C ratio as the main indicator. The results show that sheep farming is financially feasible at small (10 head), medium (50 head), and large (±100 head) scales, with R/C ratios of 1.34, 1.19, and 1.13, respectively. These findings indicate that small-scale enterprises are relatively more efficient in utilizing local resources. Strengthening infrastructure, improving access to capital, and enhancing farmers’ managerial skills, supported by empowerment programs through breeding systems and transparent marketing, are crucial strategies to improve business sustainability and strengthen farmers’ bargaining power. These strategies also contribute to supporting food security based on sheep meat.